Race for Second Place? Explaining East-West Differences in Anti-Muslim Sentiment in Germany - Kalter, Frank; Foroutan, Naika (Frontiers in Sociology, 2021)
It has been shown that anti-Muslim sentiment is more pronounced in East Germany than in West Germany. In this paper, we discuss existing explanations and add to them. We argue that some East Germans see themselves as a disadvantaged group in competition with other minorities, such as Muslims, for social recognition by West Germans; they are in what we call a ‘race for second place’. Based on social identity theory, we expect that this might be particularly true for those who explicitly self-identify as East Germans. The theoretical discussion carves out the role of ‘perceived non-recognition’ and ‘outgroup mobility threat’ as important concepts within the conflicts of belonging. We use unique data from the survey ‘Postmigrant Societies: East-Migrant Analogies’ for a comprehensive empirical analysis. We find that factors related to pre-existing arguments – such as socioeconomic and demographic variables, personality traits, or contact – can capture much of the group differences in anti-Muslim sentiment, but that they do not fully apply to those who were born and still live in the East and who explicitly self-identify as East Germans. For this subgroup, perceived non-recognition adds to the empirical models and outgroup mobility threat has a stronger effect.